Results of the analysis of intra-observer and inter-observer discrepancies in the assessment of some non-metric dental traits - Leybova N.A.; Chirkova A.Kh. (Вестник археологии, антропологии и этнографии, 2023)
For the first time in Russian odontology, this paper presents the results of the analysis of intra-observer and inter-observer discrepancies in the determination of non-metric dental traits. The basis for the work was the materials collected in 2022 in the western regions of the Republic of Tuva during the Tuva ethnographic and anthropological expedition of TuvSU-CPI under the direction of E.V. Ayizhy (Candidate of Historical Sciences, TuvSU). The aim of the expedition was comprehensive biological and anthropological investigation of the local population. The programme included collecting the data on somatometry, cephalometry, cephaloscopy, odontology, dermatoglyphics, panoptic anthropological portrait photography, and social survey. Due to the fact that two experts in odontology worked in the expedition, it was possible to conduct a comparative analysis of their independent determinations. An important factor appeared to be that in the Tuva expedition, for the first time in the practice of mass population-anthropological investigations, an intraoral 3D scanner was employed, which provided a rare opportunity to test the field determinations made by the researcher. This paper is concerned with the results of intra- and inter-observer correlations in the determination of non-metric dental traits by different recording techniques. Following the programme adopted in Russian odontology, during the expedition, there were 504 people examined and 331 wax impressions of teeth obtained. The complete programme of the odontological examination included visual inspection and description of the traits with the aid of a dental mirror. Using the intraoral 3D scanner Medit I500, in total 202 scans were obtained. The analysis consisted of several levels of intra- and inter-observer correlations and included three stages of connexive experiments aimed at the assessment of the nonmetric dental traits observed in the expedition and on the 3D models. The study is based upon the use of the empirical and statistical methods. At all stages of the analysis, there were no intra- and inter-observer discrepancies recorded in the assessment of the diastema, crowding, and reduction of lateral incisors. The most difficult feature for recording appeared to be the prominence of the shovelling of upper incisors. In its assessment, statistically significant differences were revealed during the intraobserver correlations. The results of the observation of the odontological traits obtained by different recording techniques, showed some systematic deviations at the individual researcher level, manifested in an overestimation of frequencies of the shovelling when determining by scans and underestimation of frequencies of the shovelling determined with the aid of the dental mirror.